(untitled) (Al-Qamar, 2019)
This research explores the struggles of South Asian Muslims in light of the model minority myth in Ayad Akhtar’s Disgraced. The protagonists’ struggles for assimilation as model minorities are thwarted due to the collective social suspicion towards Muslim identities. In Disgraced, the protagonist Amir begins as a successful, assimilated model minority, a status he has achieved through a rejection of his own Muslim identity. He has, for example, changed his last name to appear of Hindu heritage to assimilate years ago and has even passed himself along at his Jewish law firm as a Hindu-American. When his Muslim identity is disclosed, his world unravels. The primary theoretical frameworks of post-colonialism and hybridity for this study have their roots in the binaries between the Orient and the Occident. The Orientalist outlook in the aftermath of colonialism has remained the foundation of the Western perception of the East.